Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Deposition of indium nitride films by activated reactive evaporation process - a feasibility study - Patil, Sheetal J.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Indium nitride (InN) films are deposited by `activated reactive evaporation (ARE)' process using parallel plate coupled nitrogen plasma (radio frequency source of 13.56 MHz) and evaporation of pure indium powder by resistive heating. Depositions are carried out by varying RF plasma power, on n-type silicon &LANGBRAC; 1 0 0&RANGBRAC; substrate, maintained at room temperature, at a nitrogen gas pressure of 1.06 x 10(-1) Pa (8 x 10 (-4) Torr). The film's crystallinity was examined by X-ray diffraction (XRD) and topography by scanning electron microscope (SEM). The diffraction pattern shows polycrystalline nature of the deposited films with characteristics of hexagonal structure. XRD peak intensity increases with increase in power. SEM observations show a smooth and pinhole free surface having improved quality of film with hexagonal structure as the power is increased from 60 to 120 W. Primary X-ray photoelectron spectroscopy (XPS) results show binding energies of the In 3d levels and N 1s level matching well with that of stoichiometric InN. Further, the refractive index of the films, measured by ellipsometry, is in the range of η = 2.79-2.91 with the variation of plasma power, which is in good agreement with the standard value for indium nitride (η = 2.9). These results indicate the feasibility of using, `activated reactive evaporation (ARE)' process for indium nitride depositions on silicon &LANGBRAC; 1 0 0&RANGBRAC; substrates maintained at room temperature. © 2004 Elsevier B.V. All rights reserved.
Keywords: activated reactive evaporation; ellipsometry; indium nitride; SEM; XRD

Deposition of PTFE thin films by RF plasma sputtering on < 100 > silicon substrates - Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Polymers have been studied extensively due to the wonderful array of properties presented by them. Polymer materials can be coated/deposited by various techniques like sputtering (magnetron, ion beam, RF or dc), plasma polymerization, etc. and can be used in coatings, paint industries, etc. The present study deals with the RF sputter deposition of poly(tetrafluoro ethylene) (PTFE), commonly known as Teflon. Depositions were carried out on mirror polished silicon (1 0 0) substrates at different powers in the range of 100-200 W. The deposition time was kept constant at 60 min. The sputtered film shows lower contact angle of 50&DEG; with water and 44&DEG; with diiodomethane, a lower interfacial tension value of 0.76 dyne/cm, indicating hydrophilicity and good adhesion of the film with the substrate. FHR indicates presence of C-F, C-F-2 bonding groups in the deposited film. Further, XPS study shows presence of CF3 (292.2 eV), CF2 (290.8 eV), C-F (288.0 eV) and C-CF (286.4 eV) moieties indicating deposition of PTFE films at higher power levels of plasma. © 2004 Elsevier B.V. All rights reserved.
Keywords: Contact angle measurement; FTIR; PTFE; RF plasma sputtering; XPS